2021
DOI: 10.1039/d1na00487e
|View full text |Cite
|
Sign up to set email alerts
|

Meso- and macroporous silica-based arsenic adsorbents: effect of pore size, nature of the active phase, and silicon release

Abstract: Arsenic pollution in ground and drinking water is one of the major problems worldwide due to the natural abundance of arsenic by dissolution from ground sediments or mining activities as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 98 publications
1
16
0
Order By: Relevance
“…Concerning the secondary silicon pollution (Table S5), the comparison between As III and As V tests reveals that the phenomenon is limited in the case of the As III species, and the silicon release is mainly affected by the pH, probably due to a weaker interaction of arsenite with the sorbent. On the contrary, the Si release observed for the As V removal tests indicated that arsenate species play a crucial role, as already observed in a previous study [39], beyond a pH effect.…”
Section: Effect Of the Ph In The As V And As Iii Test Removal By Fe Iii -Based Sorbentssupporting
confidence: 68%
See 3 more Smart Citations
“…Concerning the secondary silicon pollution (Table S5), the comparison between As III and As V tests reveals that the phenomenon is limited in the case of the As III species, and the silicon release is mainly affected by the pH, probably due to a weaker interaction of arsenite with the sorbent. On the contrary, the Si release observed for the As V removal tests indicated that arsenate species play a crucial role, as already observed in a previous study [39], beyond a pH effect.…”
Section: Effect Of the Ph In The As V And As Iii Test Removal By Fe Iii -Based Sorbentssupporting
confidence: 68%
“…The comparison between Comp and the bare silica matrix (Figure S1), reveals a decrease of 10% of surface area and 11% of pore volume in the first one, as expected after the impregnation process. The PSD is instead centered, for both samples, at about 8 nm, suggesting the formation of isolated NPs inside the pores in spite of a uniform layer [39,60,61]. a, b, and c: cell parameters; D XRD 1 and D XRD 2 : crystallite sizes; D TEM 1 and D TEM 2 : particle sizes; S BET : surface area; V p : pore volume; D p : pore diameter.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Various silica-based composites with good performances in the removal of heavy metal ions, or oxyanions, have been lately reported. 24 28 Among them, selective and efficient adsorption of arsenic ions by the amino-functionalized silica, 24 , 25 surface-ion imprinted silica, 26 or quaternary amine-functionalized silica 28 have been reported in the last decade. Porous silica has been used as a suitable host for numerous functional polymers, such as anionic hydrogels, 29 anion exchangers, 30 and amidoxime ligands.…”
Section: Introductionmentioning
confidence: 99%